Revitalisasi Peran UIN Sumatera Utara Melalui KKN 105 di Desa Bulu Cina untuk Mewujudkan Masyarakat yang Bermartabat Tahun 2022 - Erti Belastari Tanjung; Yulianda Tasya; Sarah Aprilia Harahap; Inggrid Adriani Paramitha Puteri; Era Fazira (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Real Work Lecture which is held in Bulu Cina village, expanse of silver sub-district in 2022 which is held annually, but in the previous year offline KKN was not held because it was still in a state of the covid-19 pandemic, and last year there was offline KKN in this village in 2016, and Alhamdulillah this year KKN is officially re-implemented offline, with the existence of KKN which is carried out offline it provides the potential for self-development for KKN 105 students to carry out field practice directly in the context of direct service and outreach to the community. The development and example of this research is a group of 105 KKN UINSU with qualitative methods (data collection, observation and documentation), with the theme Revitalizing the Role of UIN North Sumatra through KKN 105 in Bulu Cina Village To Create a Dignified Society. The results of this study illustrate that KKN activities are direct examples of community service and the important role of students which is still carried out with several activities, namely building the village where KKN is located.